The Chinese in Cuba, 1847-now - García Triana, Mauro (AsiaWorld., 2009)
The Chinese community in Cuba in the nineteenth century was second only in size to that in the United States. This book of essays and documents looks at the community's revolutionary history and its contemporary evolution.